2021
DOI: 10.1590/1516-3180.2021.0106.r1.0904221
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion index: Could this be a new triage tool for upper gastrointestinal system bleeding in the emergency department? A prospective cohort study

Abstract: BACKGROUND: Many scoring systems for predicting mortality, rebleeding and transfusion needs among patients with upper gastrointestinal bleeding (UGIB) have been developed. However, no scoring system can predict all these outcomes. OBJECTIVE: To show whether the perfusion index (PI), compared with the Rockall score (RS), helps predict transfusion needs and prognoses among patients presenting with UGIB in emergency departments. In this way, critical patients with transfusion needs can be identified at an early s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The finding of the current study is supported by a study of using perfusion index as a tool for fluid replacement of upper GIT bleeding patients where there was a significant relation between MAP of both groups (Firat et al, 2021). Other review studies suggested that the use of a standardized and bundled care can improve patients perfusion through maintaining normal MAP in patients with upper GIT bleeding (Haigh, 2022;Siau et al, 2020).…”
Section: Discussionsupporting
confidence: 72%
“…The finding of the current study is supported by a study of using perfusion index as a tool for fluid replacement of upper GIT bleeding patients where there was a significant relation between MAP of both groups (Firat et al, 2021). Other review studies suggested that the use of a standardized and bundled care can improve patients perfusion through maintaining normal MAP in patients with upper GIT bleeding (Haigh, 2022;Siau et al, 2020).…”
Section: Discussionsupporting
confidence: 72%
“…The PI in emergency departments helps in the identification of the need for transfusion [ 20 ]. It also helps to estimate the mortality risk in patients presenting with upper gastrointestinal bleeding and mortality in mechanically ventilated patients [ 21 , 22 ]. Moreover, it helps in the detection of hypotension during anesthesia and to identify the effectiveness of ganglion blocks [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%